Hybrid large‐eddy simulation with adaptive downstream anisotropic eddy viscosity model. (30th June 2022) - Zhang, Wanjia; Shih, Tom I‐P.
Abstract: Turbulence pervades most flows of engineering interest, and its prediction remains a challenge on both accuracy and cost. One promising predictive approach that reduces cost combines large‐eddy simulation (LES) with simulation based on Reynolds averaged Navier–Stokes equations (RANS). This study presents a method to overcome stability and accuracy issues associated with these hybrid LES‐RANS methods. The method developed involves extracting the Reynolds stresses from the upstream LES solution and then using that information to convert the downstream RANS model from a scalar eddy‐viscosity model to an anisotropic nonlinear eddy‐viscosity model. The method developed differs from the downstream tensorial eddy‐viscosity model by being independent of the coordinate system. The method developed was evaluated by computing film cooling of a flat plate with the coolant injected through one row of circular holes. Results obtained show instabilities at the LES‐to‐RANS interface to be eliminated. Also, the method developed yielded solutions that compare reasonably well with those from LES, even though a significant portion of the flow is computed by the adapted anisotropic RANS model instead of LES, which significantly reduced the number of grid points and computational time needed. Since modification of the downstream RANS model is based on information extracted from the upstream LES solution, the method developed is adaptive to the problem being studied. Abstract : This study presents a method which extracts the Reynolds stresses from the upstream LES solution and then uses that information to convert the downstream RANS model to an anisotropic nonlinear eddy viscosity model to overcome stability and accuracy issues associated with hybrid LES‐RANS methods. The method developed was evaluated by computing film cooling of a flat plate with the coolant injected through a row of circular holes. Results obtained are almost as accurate as those from LES and instabilities at the LES‐to‐RANS interface are eliminated.